Analisis Peta Kemampuan Keuangan Provinsi Sebelum dan Setelah Otonomi Daerah - Ratna Christianingrum; Ade Nurul Aida (Pusat Kajian Anggaran, 2020)
This analysis aims to study the implementation of regional autonomy in terms of the regional financial capacity before the existence of regional autonomy and to compare the regional financial capabilities after the existence of regional autonomy. The parameters used are the calculation and analysis of PAD performance using the index method, the quadrant method, and the difference test.The results of the analysis show that after regional autonomy the financial capacity of the region has decreased, as indicated by the number of provinces that have high IKK has decreased from before regional autonomy. In addition, based on the test results, it is found that the implementation of decentralization does not improve the financial capacity of provinces in Indonesia. The map of the financial capacity of the provinces in Indonesia before and after regional autonomy also shows that changes in the regional capacity map are significant. A total of 15 provinces have a decline in the classification of their regional financial capacity. Meanwhile, only 2 provinces have an increase in the classification of regional financial capacity. For this reason, the government encourages local governments to be able to innovate in finding potential sources of regional income.